The Application of Cooperative Principle in EFL Classroom Interaction - Yusro, Alfin; Sutopo, Djoko; Yuliasri, Issy (English Education Journal, 2020)
In classroom interaction, we sometimes find misunderstanding between teacher and student or among the students. Grice said that cooperative principles can lead the speakers and hearers to uncooperative conversation and misunderstanding about the message delivered (Grice: 1989). Based on that theory, an investigation about observance and non-observance of the maxim should be done to understand how they apply the cooperative principles in classroom interaction. The objective of the studies are: (1) to analyze EFL classroom interaction in order to explain the way cooperative principles are applied, (2) to analyze EFL classroom interaction in order to explain the way participants violate the maxim (3) to analyze the most frequent violation in non-observance of the maxim. In this study, I use descriptive qualitative method. The data of this study was the transcription of EFL classroom interaction between teacher and students. The interaction was natural interaction without any intervention from me. The findings of this research showed that teachers and students not only observed the maxim but also violate the maxim in the EFL classroom interaction.